Adsorption Process for Acrylic Acid Removal from Wastewater - Nur Sakinah Mat Saad (Universitas Ahmad Dahlan, 2016)
The objectives of this study were to develop the mathematical model of the adsorption process of the acrylic acid by using the activated carbon and also to validate the simulation of the adsorption process by using the experimental data. Simulation of the adsorption process is necessary to understand the acrylic acid removal using adsorption process. Acrylic acid is removed from the waste water because it can cause serious damage to the environment due to its high toxicity for the aquatic organisms. As a conclusion, the objective is expected to achieve. The new mathematical model of the adsorption process of the acrylic acid by using the activated carbon can be created. The validation of the simulation is carried out to compare the simulation data with the experiment data.